PELATIHAN SUMBER DAYA MANUSIA DI PERUSAHAAN DEALER DI CIANJUR - Kartanegara, Haruman Taufik; Saripah, Iip; Kamil, Mustofa; Saepudin, Asep (Jurnal Empowerment, 2025)
Training is a systematic process of providing knowledge, skills and behavior to individuals or groups in order to increase their abilities and productivity in work or daily life. Through training activities, employees have a great opportunity to absorb new values that have not existed so far, so that with this new pattern they can improve their profession in carrying out the tasks assigned to them . This article was prepared by utilizing literature as a writing method. In addition, the writer also confirms the information obtained with the interview data. The results of the study show that the superiority of HR training is for employee conducted by PT. Srikandi Diamond Motors Mitsubishi Motors Authorized Dealer Cianjur is upgrading performance very helpful employees for company nor employee That Alone supported training program _ _ facilities , resource persons , materials , appropriate Standard International Training (SIT), but standard training company must still minimize counter with situations and conditions local .